VALIDATION OF SPECTROPHOTOMETRY METHOD FOR DETERMINATION OF (+)-CATECHIN IN ETHYL ACETATE FRACTION OF GAMBIR EXTRACT (Uncaria gambir Roxb.) - Nanang Yunarto; Uud Nourma Reswandaru; Indah Sulistyowati; Indhira Oliffia Prameswari; Qotrunnada Linggar Pinanditi; Tri Madesa Patadungan (Balai Besar Penelitian dan Pengembangan Tanaman Obat dan Obat Tradisional, 2021)
ABSTRACT Gambir leaves (Uncaria gambir Roxb.) is a plant that has been widely used by people for traditional medicine. The main compound of gambir extract is a (+)-catechin that has been proven as anti-dental plaque, antioxidant, antibacterial, and antihyperlipidemic. This study aims to validate a method for the quantitative determination of catechin in ethyl acetate fraction of gambir extract based on spectrophotometry. The validation was conducted by measuring the linearity, accuracy, and ruggedness of the method that fulfills the requirements along with the limit of detection (LoD) and limit of quantification (LoQ) determination. Determining the precision (based on %RSD and CV), 100 ppm of catechin were made to 7 replicates while accuracy was evaluated by calculating the recovery. The ruggedness of the method is determined by analyzing it on a different day. The linearity was determined by assessing the r-value on the relation between the absorbance curve and standard series concentration. The LoD and LoQ could be calculated based on the standard curve equation. The results showed the method fulfilled the linearity requirement with R 0.9996; had precision in 1.23% RSD; had accuracy in the range of 100.80% to 101.64%; the method ruggedness was not significantly different; had 3.85 ppm of LoD and 12.84 ppm of LoQ. The validation method showed a valid result, and the method can be used for routine analysis on the measurement of catechin in ethyl acetate fraction of gambir extract. Keywords: Catechin, Uncaria gambir, Method Validation, Spectrophotometry ABSTRAK Daun gambir (Uncaria gambir Roxb.) merupakan tanaman yang telah banyak dimanfaatkan masyarakat dalam pengobatan tradisional. Senyawa utama ekstrak gambir adalah (+)-katekin yang telah terbukti sebagai anti plak gigi, antioksidan, antibakteri, dan antihiperlipidemia. Penelitian ini bertujuan untuk memvalidasi suatu metode penentuan kuantitatif katekin dalam fraksi etil asetat ekstrak gambir secara spektrofotometri. Validasi dilakukan dengan mengukur linearitas, akurasi, dan kekasaran metode yang memenuhi persyaratan beserta penetapan Limit of Detection (LoD) dan Limit of Quantification (LoQ). Penentuan presisi (berdasarkan %RSD dan CV), 100 ppm katekin dibuat 7 ulangan sedangkan akurasi dievaluasi dengan menghitung perolehan kembali. Kekasaran metode ditentukan dengan menganalisisnya pada hari yang berbeda. Linearitas ditentukan dengan mengukur nilai r pada hubungan antara kurva absorbansi dan konsentrasi seri standar. Berdasarkan persamaan kurva standar, maka LoD dan LoQ dapat dihitung. Hasil penelitian menunjukkan metode memenuhi syarat linearitas dengan R 0,9996; memiliki presisi di 1,23% RSD; memiliki akurasi pada kisaran 100,80% sampai dengan 101,64%; kekasaran metode tidak berbeda nyata; memiliki 3,85 ppm LoD; dan 12,84 ppm LoQ. Validasi menunjukkan hasil yang valid, dan metode tersebut dapat digunakan untuk analisis rutin pada pengukuran katekin dalam fraksi etil asetat ekstrak gambir. Kata kunci: Catechin, Uncaria gambir, Validasi Metode, Spektrofotometri